Amanat Agung Yesus dan Model Kepemimpinan Kristiani - Leonard David Rengkuan (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
The Great Commission of Jesus Christ in Matt. 28:18-20 laid the foundation for the institutionalization of Baptism in the Church, due to the task of proclaiming the Good News, baptizing and leading the faithful. In reality, Christians are often less aware of the true meaning of Christian leadership in their ministerial duties and relevant models of Christian leadership. Using literature study, this article provides a review of the Great Commission and some ideas about Christian leadership. Christian leadership is discussed in order to offer at the end, a model of Christian leadership to implement this Great Commission, namely Servant Leadership.